Toward Transgender Affirmative Social Work Education. (2nd July 2016) - Austin, Ashley; Craig, Shelley L.; McInroy, Lauren B.
ABSTRACT: Social work has professional and academic standards consistent with transgender affirmative education and practice. Nevertheless, a growing body of research suggests that transgender issues are largely absent from social work education, resulting in practitioners who are uninformed or biased against transgender issues. The present study expands the literature through a mixed methods study exploring perceptions of transgender issues in social work education from the perspectives of transgender social work students ( n = 97). Quantitative and qualitative analyses reveal barriers to transgender affirmative social work education including (1) transphobic microaggressions within classroom and field settings, (2) the absence of transgender specific education and expertise, and (3) the general lack of visibility of transgender issues. Recommendations for transgender affirmative social work education are provided.